A trauma retorikája Salman Rushdie regényeiben: Az éjfél gyermekei és a Szégyen - Györke, Ágnes (Studia Litteraria, 2011)
My paper investigates the rhetoric of national traumas in Salman Rushdie’s Midnight’s Children and Shame. I argue that the birth of India and Pakistan are depicted as traumatic events in these novels in the sense in which Cathy Caruth uses the term: they appear as unacknowledged, unclaimed experiences. The metaphor of the noise speaks about these moments in Midnight’s Children, the miraculous noise of the children’s conference, which is the allegory of the Indian nation in the novel, whereas in Shame the grotesque cacophony of cultural encounters, which create the “palimpsest” of Pakistan. The texts find different means to deal with these experiences: in Midnight’s Children the discovery of the children’s noise is traumatic for the main character, who is unable to make sense of the incident, and redefines the metaphor he articulates in this moment several times, trying to attribute some kind of meaning to the elusive, unclaimed experience. In Shame the grotesque music simply becomes repressed: instead of coming to terms with the trauma of their shameful night, the “three mothers” resolve never to feel this emotion again, and lock themselves in their enormous, silent house. I argue that whereas Midnight’s Children manages to transform the trauma into narrative memory, however inadequately, Shame fails to find any means to integrate the experience, which inevitably leads to the reassertion of silence at the end of the novel.